Relações sociais, processos de dominação e estratégias de enfrentamento no sistema de aviamento em Barcelos-AM - (:unkn) unknown (Universidade Federal do Amazonas, 2019)
Recent mobilizations based on denunciations concerning slave labor in designated production units of "piaçabais" in Barcelos-AM triggered a process of judicialization of labor relations and a series of State acts for this municipality. The social relations, especially economic and power, between the agents involved in the extractive relations of the fibers of piaçaba, denominated "piaçabeiros" and the traders of this fiber known as "patrões" are object of study of this thesis. Between 2007 and 2017 I have been carrying out fieldwork and building a research relationship with the social agents related to the subject of this thesis. Interviews, direct observation, GPS survey, photographic and audiovisual records, workshops and courses were carried out during this discontinuous period. The collective identity of the "piaçabeiro", today, is built in a space of relations that distinguishes between those who extract the fibers of the piaçaba, and know the entire process of extraction from a series of traditional knowledge, which are recognized as such and have their labor force expropriated by those who commercialize this production, called "patrões". Since the colonial period, the historical processes related to extractivism in the Amazon have been marked by a relationship of power and domination, be it with the so-called "drogas do sertão in the rubber industry in the nineteenth and mid-twentieth centuries, and even in the construction of Development Plans for the Amazon in the 20th century. In this way, the practices of extractivism had little space in public policies, having developed in the Amazon under the aegis of patronage, with the "system of aviamento". This system based on the unequal exchange between traders and extractive workers, is characterized by the advance of merchandise on credit. The denunciations received by the MPF and MTE on the extractive work of the piaçaba if it is defined as "work analogous to slavery" is justified by the characterization of debt bondage, the degrading conditions of work, the exhaustive days and restriction in the right to move. Apart from an economic debt imposed on these workers, there is also the debt morality, from which honor, guilt and stigma act as instruments of domination. In that case, honor and credit go together. The mechanisms of resistance and coping that the "piaçabeiros" play, such as the mockery in the weight of the production, the denunciations, and the disregard of the stigmas, are used when these agents perceive their situation of immobilization of the work force. This awareness leads to the confrontation of centuries of this immobilization, although not abruptly, can be a way to weaken the system of aviamento, this possibility has been seen with the experiences of the so-called "independent piaçabeiro".
Keywords: Piaçabeiros; Relações sociais; Enfrentamento e resistência; Barcelos (município); CIÊNCIAS HUMANAS: ANTROPOLOGIA